Uveitis secondary to leishmaniasis immune reconstitution syndrome in a HIV-positive patient. (June 2016) - Davies, Olubanke; Allen, Felicity; Gruener, Anna M; Simons, Rebecca; Graham, Elizabeth M; Larbalestier, Nick
We describe the case of a HIV-positive patient treated for visceral leishmaniasis who developed uveitis as part of a leishmaniasis immune reconstitution syndrome. Visceral leishmaniasis is increasingly found in HIV-positive adults. Its ophthalmic manifestations can range from relatively minor to complicated anterior uveitis, leading to secondary glaucoma and loss of vision. Clinicians caring for people living with HIV should be alert to the complications of leishmaniasis that can occur before and during treatment.